Evidence From the Trauma-Film Paradigm That Traumatic and Nontraumatic Memories Are Statistically Equivalent on Coherence. (May 2022) - Taylor, Andrea; Zajac, Rachel; Takarangi, Melanie K. T.; Garry, Maryanne
There is contention in the scientific literature about the coherence of people's memories for trauma: Sometimes, traumatic memories are rated as less coherent than nontraumatic memories; other times, they "look" very similar. But several methodological challenges invite counter-explanations that hinder the interpretation of these findings. We set out to address these challenges by adopting a trauma-film-paradigm approach to examine the coherence of traumatic and nontraumatic memories. We developed a new set of materials for the trauma-film paradigm and then used these materials to examine the relative coherence of traumatic and various nontraumatic memories. We found that traumatic memories were not only fairly coherent but also statistically equivalent to their nontraumatic counterparts. Our hope is that scientists use these materials in experiments that complement the existing autobiographical-memory literature and allow for a greater understanding of the relation between memory and dysfunction.